2008
DOI: 10.1152/japplphysiol.00900.2007
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated protein kinase phosphorylates transcription factors of the CREB family

Abstract: AMP-activated protein kinase (AMPK) has been identified as a regulator of gene transcription, increasing mitochondrial proteins of oxidative metabolism as well as hexokinase expression in skeletal muscle. In mice, muscle-specific knockout of LKB1, a component of the upstream kinase of AMPK, prevents contraction- and 5-aminoimidazole-4-carboxamide-1-beta-D-ribofuranoside (AICAR)-induced activation of AMPK in skeletal muscle, and the increase in hexokinase II protein that is normally observed with chronic AICAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
158
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(162 citation statements)
references
References 58 publications
3
158
1
Order By: Relevance
“…Phosphorylation of histone deacetylase 5 (HDAC5) by AMPK increases HDAC5 binding to 14-3-3 protein, and the subsequent nuclear export of the complex allows transcription factor-mediated regulation of glucose transporter 4 (GLUT4) gene expression (41). The gene encoding the glucose-metabolizing protein hexokinase II (HKII) contains a cAMP response element in its promoter region (49), and AMPK regulates the activity of the transcription factor cAMP response element-binding protein through direct phosphorylation (53). Experiments performed in vitro and in cell culture have shown that AMPK phosphorylates peroxisome proliferator-activated receptor-␥ coactivator-1␣ (PGC-1␣) (23), which is known as a major transcriptional regulator of genes encoding oxidative proteins in skeletal muscle (36).…”
mentioning
confidence: 99%
“…Phosphorylation of histone deacetylase 5 (HDAC5) by AMPK increases HDAC5 binding to 14-3-3 protein, and the subsequent nuclear export of the complex allows transcription factor-mediated regulation of glucose transporter 4 (GLUT4) gene expression (41). The gene encoding the glucose-metabolizing protein hexokinase II (HKII) contains a cAMP response element in its promoter region (49), and AMPK regulates the activity of the transcription factor cAMP response element-binding protein through direct phosphorylation (53). Experiments performed in vitro and in cell culture have shown that AMPK phosphorylates peroxisome proliferator-activated receptor-␥ coactivator-1␣ (PGC-1␣) (23), which is known as a major transcriptional regulator of genes encoding oxidative proteins in skeletal muscle (36).…”
mentioning
confidence: 99%
“…Both CREB1 and ATF1 are phosphorylated on homologous motifs by cAMP-dependent protein kinase (protein kinase A, PKA) and 5'-AMPK-activated protein kinase (AMPK) 8,9 .…”
Section: Atf1mentioning
confidence: 99%
“…AMPK may modify transcription via phosphorylation of a large and growing number of transcription factors and chromatin proteins 13,[15][16][17][18][19][20][21] . Critically, these include ATF1 9 . Purified AMPK phosphorylated recombinant purified ATF1 in an in vitro kinase assay in a cell-free system, in a paper defining AMPK-mediated phosphorylation of CREB family proteins in vivo in skeletal muscle during exercise 22 .…”
Section: Ampkmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an increase in the intracellular free AMP/ATP ratio during exercise results in the activation of AMP-activated protein kinase (AMPK) 30) . Activated AMPK regulates PGC-1α via both the posttranslational phosphorylation of preexisting PGC-1α 31) and increased PGC-1α transcription by activating transcription factors targeted to their regulatory elements 7,32) . An oscillatory change in the intracellular calcium ion concentration during excitation-contraction coupling activates Ca 2+ activated enzymes calcium/calmodulin dependent protein kinase Ⅱ (CaMKⅡ) 33) .…”
Section: Intracellular Signaling Involved In Endurance Traininginducementioning
confidence: 99%